2009
DOI: 10.2353/jmoldx.2009.090078
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Reference Materials for MTHFR, SERPINA1, RET, BRCA1, and BRCA2 Genetic Testing

Abstract: Well-characterized reference materials (RMs) are integral in maintaining clinical laboratory quality assurance for genetic testing. These RMs can be used for quality control , monitoring of test performance, test validation , and proficiency testing of DNA-based genetic tests. To address the need for such materials, the Centers for Disease Control and Prevention established the Genetic Testing Reference Material Coordination Program (GeT-RM), which works with the genetics community to improve public availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Gaucher disease, mucolipidosis IV, Neimann-Pick disease and Tay-Sachs disease) [22], cystic fibrosis [23], Huntington's disease [24], methylene tetrahydrofolate reductase-related homocysteinemia, a1-anti trypsin deficiency, multiple endocrine neoplasia and BRCA1-and BRCA2-related cancers [25]. Genomic DNA material was tested in between three and ten clinical genetic laboratories for each of these disorders using a variety of genetic assays, including DNA sequence analysis.…”
Section: Reviewmentioning
confidence: 99%
“…Gaucher disease, mucolipidosis IV, Neimann-Pick disease and Tay-Sachs disease) [22], cystic fibrosis [23], Huntington's disease [24], methylene tetrahydrofolate reductase-related homocysteinemia, a1-anti trypsin deficiency, multiple endocrine neoplasia and BRCA1-and BRCA2-related cancers [25]. Genomic DNA material was tested in between three and ten clinical genetic laboratories for each of these disorders using a variety of genetic assays, including DNA sequence analysis.…”
Section: Reviewmentioning
confidence: 99%
“…2 The first major limitation is the lack of controls for genes in rare conditions, whereas another issue is the availability of having a source of well-characterized, consistent, and renewable controls for each DNA variant tested. 5,6 A similar problem exists with proficiency testing for genetic laboratories, where the limitations of analyte-specific testing in the NGS era has led the College of American Pathologists to support the move toward a methods-based proficiency testing strategy. The College of American Pathologists concluded that a methods-based approach allows the standardization of proficiency testing among laboratories that use vastly different NGS panels and provides a practical, efficient, cost-effective, and thorough mechanism to administer testing.…”
Section: Discussionmentioning
confidence: 99%
“…The Center for Disease Control (CDC) has developed a process whereby the commutability of readily available materials have been tested in numerous laboratories (13). Additionally, the rapid evolution of technologies and methodologies used in molecular diagnostic testing exceeds the capacity to generate reference materials.…”
Section: Discussionmentioning
confidence: 99%